Microbial Air Contamination in a Dental Setting Environment and Ultrasonic Scaling in Periodontally Healthy Subjects: An Observational Study - Boccia, Giovanni; Di Spirito, Federica; D’Ambrosio, Francesco; De Caro, Francesco; Pecora, Domenico; Giorgio, Riccardo; Fortino, Luigi; Longanella, Walter; Franci, Gianluigi; Santella, Biagio; Amato, Massimo (International journal of environmental research and public health, 2023)
The risk of microbial air contamination in a dental setting, especially during aerosol-generating dental procedures (AGDPs), has long been recognized, becoming even more relevant during the COVID-19 pandemic. However, individual pathogens were rarely studied, and microbial loads were measured heterogeneously, often using low-sensitivity methods. Therefore, the present study aimed to assess microbial air contamination in the dental environment, identify the microorganisms involved, and determine their count by active air sampling at the beginning (T0), during (T1), and at the end (T2) of ultrasonic scaling in systemically and periodontally healthy subjects. Air microbial contamination was detected at T0 in all samples, regardless of whether the sample was collected from patients treated first or later; predominantly Gram-positive bacteria, including Staphylococcus and Bacillus spp. and a minority of fungi, were identified. The number of bacterial colonies at T1 was higher, although the species found were similar to that found during the T0 sampling, whereby Gram-positive bacteria, mainly Streptococcus spp., were identified. Air samples collected at T2 showed a decrease in bacterial load compared to the previous sampling. Further research should investigate the levels and patterns of the microbial contamination of air, people, and the environment in dental settings via ultrasonic scaling and other AGDPs and identify the microorganisms involved to perform the procedure- and patient-related risk assessment and provide appropriate recommendations for aerosol infection control.